Tumor Targeting via siRNA-COG3 to Suppress Tumor Progression in Mice and Inhibit Cancer Metastasis and Angiogenesis in Ovarian Cancer Cell Lines - Ijabi, Janat; Ijabi, Roghayeh; Roozehdar, Parisa; Kaminsky, Zachary A.; Moradi-Sardareh, Hemen; Tehranian, Najmeh; Ahmed, Naveed (MicroRNA, 2024)
Background: The COG complex is implicated in the tethering of retrograde intra-Golgi vesicles, which involves vesicular tethering and SNAREs. SNARE complexes mediate the invasion and metastasis of cancer cells through MMPs which activate growth factors for ECM fragments by binding to integrin receptors. Increasing MMPs is in line with YKL40 since YKL40 is linked to promoting angiogenesis through VEGF and can increase ovarian cancer (OC) resistance to chemotropic and cell migration. Objective: The aim of this study is an assessment of siRNA-COG3 on proliferation, invasion, and apoptosis of OC cells. In addition, siRNA-COG3 may prevent the growth of OC cancer in mice with tumors. Methods: Primary OC cell lines will be treated with siRNA-COG3 to assay YKL40 and identified angiogenesis by Tube-like structure formation in HOMECs. The Golgi morphology was analyzed using Immunofluorescence microscopy. Furthermore, the effects of siRNA-COG3 on the proliferation and apoptosis of cells were evaluated using MTT and TUNEL assays. Clones of the HOSEpiC OC cell line were subcutaneously implanted in FVB/N mice. Mice were treated after two weeks of injection of cells using siRNA-COG3. Tumor development suppression was detected by D-luciferin. RT-PCR and western blotting analyses were applied to determine COG3, MT1- MMP, SNAP23, and YKL40 expression to investigate the effects of COG3 gene knockdown. Results: siRNA-COG3 exhibited a substantial effect in suppressing tumor growth in mice. It dramatically reduced OC cell proliferation and triggered apoptosis (all p < 0.01). Inhibition of COG3, YKL-40, and MT1-MPP led to suppression of angiogenesis and reduction of microvessel density through SNAP23 in OC cells. Conclusion: Overall, by knockdown of the COG3 gene, MT1-MMP and YKL40 were dropped, leading to suppressed angiogenesis along with decreasing migration and proliferation. SiRNACOG3 may be an ideal agent to consider for clinical trial assessment therapy for OC, especially when an antiangiogenic SNAR-pathway targeting drug.
Keywords: MT1-MPP